The Influence Of Price And Payment Method On Purchase Decisions At Sakinah Sukolilo Supermarket Surabaya - Purnama, Sultan Karima Adytia; Arfani, Mochammad; Ayuningtiyas, Galuh Ajeng; Sarwani (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of prices and payment methods on consumer purchase decisions at Sakinah Sukolilo Supermarket Surabaya. Changing shopping behaviors and the increasing use of digital payments encourage the need to evaluate both factors in the context of local retail. The study used a quantitative approach with a sample of 96 respondents obtained through the Cochran formula. Data were collected using a Likert scale questionnaire and analyzed through validity, reliability, classical assumptions, and multiple linear regression tests. The results of the study show that prices and payment methods have a positive and significant effect both partially and simultaneously on purchase decisions. An Adjusted R² value of 0.620 indicates that both variables explain 62% of the variation in purchasing decisions. Payment methods are the dominant variable with the highest beta coefficient value. These findings confirm that the ease and efficiency of digital payments and competitive pricing play an important role in increasing consumers' propensity to make purchases.